The agreement / by Karen Stokkendal Poulsen. - Poulsen, Karenl, 1964- (Filmakers Library, 2014)
World history is in the making when EU chief negotiator Robert Cooper has to settle an agreement on stable co-existence between Kosovo and Serbia. Stakes are high but in spite of the seriousness of the negotiations, they turn out to be surprisingly funny and carried out with style and charm by these three fantastic characters. It's the last territorial conflict of Europe and it's crucial for the EU to prove its ability to make peace in its own backyard. This is diplomacy behind the scenes.